2017
DOI: 10.1177/0961203317694257
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors to predict the development of chronic kidney disease in patients with lupus nephritis

Abstract: Objectives We analyzed the clinical follow-up results of 88 lupus nephritis patients to find prognostic factors for the development of chronic kidney disease in ethnically homogeneous Korean patients with biopsy-proven lupus nephritis. Methods Sociodemographic, clinical, laboratory, and treatment-related data at the time of kidney biopsy and during follow-up were obtained. Renal biopsy specimens were reclassified according to the International Society of Pathology/Renal Pathology Society classification, separa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Previous studies have mainly focused on the achievement of CR, which is defined as a UPCR of <0.5 at six months after induction treatment. 10,[12][13][14][15][16] A recent study by Hanaoka et al 7 suggested a novel concept of deep remission, which might be a more beneficial therapeutic target than the present recommendations regarding prevention of renal flare. We adopted this concept and expanded this previous work to identify the risk factors of the development of CKD in proliferative LN, focusing on the impact of stringent CR.…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have mainly focused on the achievement of CR, which is defined as a UPCR of <0.5 at six months after induction treatment. 10,[12][13][14][15][16] A recent study by Hanaoka et al 7 suggested a novel concept of deep remission, which might be a more beneficial therapeutic target than the present recommendations regarding prevention of renal flare. We adopted this concept and expanded this previous work to identify the risk factors of the development of CKD in proliferative LN, focusing on the impact of stringent CR.…”
Section: Discussionmentioning
confidence: 79%
“…The SLR identified that, at the time of LN diagnosis, (i) compromised kidney function, 21 28 (ii) hypertension 27 29 and (iii) increased patient age 30 32 have been associated with adverse long-term kidney outcomes. With regard to histologic features, proliferative forms of LN (histologic classes III and IV according to the 2003 International Society of Nephrology/Renal Pathology Society (ISN/RPS) classification), increasing percentage of crescents and higher National Institutes of Health histologic activity and chronicity scores have all been associated with adverse long-term kidney outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…In individual studies, use of HCQ has been associated with a lower risk for tubulointerstitial inflammation on kidney biopsy 56 and with a higher likelihood for complete response at 1 year. 57 Regarding long-term outcomes, HCQ use has been associated with reduced risk for ESKD/chronic kidney disease (CKD) or doubling of serum creatinine (adjusted HR 0.18–0.40); 27 58 59 a posthoc analysis of the Aspreva Lupus Management Study (ALMS) RCT showed that lack of treatment with antimalarials had more than double risk for treatment failure (defined as death or ESKD or sustained doubling of serum creatinine or renal flare or requirement for rescue therapy) during the maintenance phase (OR 2.4, p = 0.02). 60 Data regarding protection from kidney flares are equivocal 61 62 ; a single study showed lower blood concentrations of HCQ in patients with LN who experienced a flare (0.59 vs 0.81 mg/L; p = 0.005).…”
Section: Resultsmentioning
confidence: 99%
“…In a discussion on periodontal therapy in patients with CKD, we must also take into consideration the influence of immunosuppressive agents. In short, a variety of CKD, such as lupus nephritis and IgA nephropathy, is commonly treated with immunosuppressive agents [76,77]. Undoubtedly, the immune response is closely associated with infection control in almost organs and tissues including oral and periodontal tissues.…”
Section: Periodontal Disease and Chronic Kidney Diseasementioning
confidence: 99%